Didyma, Türkei: Konsolidierung der Umfassungsmauer des Tempelgebietes (sog. Mandramauer) - Bumke, Helga; von Gaisberg, Elgin (e-Forschungsberichte des DAI, 2023)
During the first German excavation period in Didyma a monumental enclosure wall of reused architectural components from the temple of Apollo was erected around the area of the temple, in part as a retaining wall against the higher ground level of the site beyond it. Since the 1970s the wall has been damaged and sections of it collapsed over time. In 2012 a project for investigating, mapping and documenting the condition and damage of this wall was started in preparation for the restoration of collapsed or unstable sections. Since the statics of one section of the wall, 5 metres high, with the terrace of the ‛oracle pension’ above were no longer safe, there was an urgent need to erect a stabilisation-construction of steel which was realised in 2014 by the DAI.